Proposed new interior design scheme for times bookstore at G-F Square Enterprise E-G-8, E-G-9,Greentown Square, Jalan Dato' Seri Ahmad Said, 30450, Ipoh Perak / Afzaniza Md Jusoh - Md Jusoh, Afzaniza (Faculty of Architecture, Planning and Surveying, 2011)
The project for this report is based on a final project of subject Interior Design. The title for this project is Proposed New Interior Design For Times Bookstore at G-F Square Enterprise E-G-8, E-G-9, Greentown Squre, Jalan Dato’ Seri Ahmad Said, 30450, Ipoh Perak. This project consist of client requirement, and ideas from students. The thing that suppose to be fill in this report are the introduction, clients, research and analysis, case study, project and design proposal.This should be apply together in ID project.This project is a project that been carry out based on information than being gathered from clients in order to find and solve problems in that space based on the client wants and needs. The cooperation between client is important because it is the main factor to finish this project sucessfully.